A Case Series of Surgically Treated Spinal Dumbbell Tumors of Critical Parent Nerve Roots: To Cut or Not to Cut?. Issue 3 (29th December 2020) - Butenschoen, Vicki Marie; Kögl, Nikolaus; Meyer, Bernhard; Thomé, Claudius; Wostrack, Maria
Abstract: BACKGROUND: Dumbbell tumors present challenging cases, with either an incomplete tumor resection or a need to sacrifice nerve roots. Published literature suggests encouraging neurological outcomes after nerve root amputation. OBJECTIVE: To determine the incidence of postoperative neurological deficits after amputating the parent nerve root. METHODS: A retrospective consecutive analysis of all patients treated for dumbbell nerve sheet tumors with a reported amputation of the functional relevant parent nerve roots C5-Th1 and L3-S1. RESULTS: Among 21 evaluated patients, minor postoperative neurological motor function deterioration occurred in 4 patients (19%). Most patients recovered to the preoperative level at the follow-up examination, and only one patient retained a new Medical Research Council (MRC) scale of 4/5 for deltoid weakness. The majority of tumors were resected at the lumbar level (nerve root L3: 28.6%, L5: 19%). Gross total resection was achieved in 90.5% of patients. Neuropathic pain was reported in one third of the patients during the long-term follow-up. CONCLUSION: Amputating critical parent nerve roots during the dumbbell tumor resections seems to result in a low incidence of postoperative motor deficits and may offer an acceptable sacrifice in otherwise only incompletely resectable dumbbell tumors. The cross-innervation of neighboring nerve roots and its, probably, per-se-reduced functionality may be a possible mechanism for maintaining motor function.